Pencegahan Anemia dan Menjaga Kesehatan Reproduksi pada Remaja Putri - Niken Pratiwi; Rubiati Hipni; Erna Fauziah; Erni Yuliastuti; Januarsih (Rena Cipta Mandiri, 2025)
Anemia among adolescent girls remains a major public health problem in Indonesia, with a prevalence of more than 30%. This condition affects learning concentration, productivity, and reproductive health in the future. Orphanages represent one of the vulnerable environments since adolescent girls are at risk of inadequate nutritional intake. This community service activity aimed to improve knowledge of adolescent girls regarding anemia prevention and reproductive health, and to obtain an overview of anemia status through hemoglobin (Hb) examination. The methods included a pre-test, interactive counseling and discussion, Hb measurement, and a post-test involving 35 adolescent girls at Muhammadiyah Girls’ Orphanage in Martapura. The results showed an increase in knowledge scores from an average of 46% at pre-test to 79% at post-test. Hb examination revealed that 62.9% of participants had normal Hb levels, while 37.1% were anemic, ranging from mild to moderate. This activity proved effective in increasing participants’ knowledge and provided objective data on their health condition. These findings highlight the importance of continuous educational programs and regular health monitoring for adolescent girls, especially in orphanage settings, to reduce anemia prevalence and support reproductive health.